Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1467-8543.2011.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Pay in China: Gender Aspects

Abstract: We provide an in‐depth analysis of gender differences in performance pay in China based on a unique dataset — the Life Histories and Social Change in Contemporary China — that provides information on the different components of pay including performance pay and base pay as well as a wide array of pay determining characteristic. The share of performance pay is documented and its determinants, including gender, analysed. Particular attention is paid to gender differences in the different dimensions of performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…See, for example, Meng (1998); Ng (2007); Wang & Cai (2008); and Zhang et al, (2008). A detailed analysis of the determinants of the share of performance pay in total compensation is provided in Xiu and Gunderson (2011). Since the mid-1990s, there has been a growing literature on gender pay differentials in China. The studies tend to find a substantial unadjusted earnings gap, 2 which has been increasing in the past two decades (i.e., the ratio of female-to-male earnings has been declining).…”
Section: Wage System Reform and Gender Pay Differentials In Chinamentioning
confidence: 99%
See 3 more Smart Citations
“…See, for example, Meng (1998); Ng (2007); Wang & Cai (2008); and Zhang et al, (2008). A detailed analysis of the determinants of the share of performance pay in total compensation is provided in Xiu and Gunderson (2011). Since the mid-1990s, there has been a growing literature on gender pay differentials in China. The studies tend to find a substantial unadjusted earnings gap, 2 which has been increasing in the past two decades (i.e., the ratio of female-to-male earnings has been declining).…”
Section: Wage System Reform and Gender Pay Differentials In Chinamentioning
confidence: 99%
“…Although research findings have shown an increasing portion of total pay in the form of bonuses (Warner 1996;Chiu, Wai-Mei Luk, and Li-Ping Tang 2002), most organizations believe that differentials in the bonus payments between individuals and between groups of individuals should be minimized so as to maintain harmonious and stable relations within the organization (Cooke 2001). Xiu and Gunderson (2011) provide more detailed analysis of the determinants of the different components of pay as well as gender or pooled weights) or the extent to which controls are added for factors such as firm ownership or occupation or rank (models 1-3). The majority (between 2/3 and 80%) of the malefemale pay gap appears to be attributable to pay differences for the same pay-determining characteristics.…”
Section: A Decomposing Gap Into Differences In Endowments and Returnmentioning
confidence: 99%
See 2 more Smart Citations
“…The career experiences (e.g., recruitment, pay, and promotion) of men and women are different in Chinese SOEs due to gender discrimination Leung (2002); Xiu and Gunderson (2013) Resourcebased view…”
Section: Gendermentioning
confidence: 99%